Mapping Allergic Diseases in Sub-Saharan Africa - Mvoundza Ndjindji, Ofilia; Djoba Siawaya, Joel Fleury (Frontiers in Allergy, 2022)
The consensus is that allergic diseases are increasing in Africa. However, this paradigm shift has not yet been translated into practice. Focused on infectious diseases (malaria, tuberculosis, HIV), health policies in Sub-Saharan Africa have often neglected the diagnosis and management of allergies. Allergic disease mapping is crucial to grasp the full extent of Africa's allergic diseases' impact. This mapping will require diverting resources to diagnose and study allergies, even more at the dawn of precision medicine.